Effectiveness of the PhET Simulation Assisted by Songs to Improve Students Critical Thinking Skills in Electrical Circuits - Maesaroh, Nur; Sutikno, Putri Yanuarita (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Critical thinking is a fundamental skill in science education, yet many elementary students struggle to develop it due to conventional teaching methods that limit active participation. Electrical circuit concepts are often presented theoretically without hands-on application, making it difficult for students to grasp them fully. As a result, they face challenges in understanding electric current flow, series and parallel circuits and assembling circuits correctly. This study investigates the effectiveness of integrating PhET simulations with songs to enhance students' critical thinking skills in learning electrical circuits. A quasi-experimental design with a Nonequivalent Control Group was used, involving 40 students selected through total sampling. The control group (Class VA) received conventional instruction supplemented with videos, while the experimental group (Class VB) engaged in learning through PhET simulations combined with song and project-based learning. Data collection included written tests based on critical thinking indicators, interviews, and documentation. Statistical analysis comprised independent t-tests and N-Gain calculations. The t-test analysis, with a calculated t-value of 9.367, showed that students in the experimental group experienced significantly higher improvements in critical thinking skills than those in the control group. The experimental class achieved an average N-Gain score of 0.83 (high category), whereas the control class reached only 0.22 (low category). This finding shows that integrating PhET simulations with songs can improve students' critical thinking skills. In addition, supporting the Project Based Learning method allows students to apply their knowledge to real-world projects, encouraging deeper exploration and problem-solving skills. This research presents an innovative method for fostering critical thinking through interactive learning. Further research can investigate its implementation in different subjects to refine and expand effective teaching strategies.